2017
DOI: 10.1097/md.0000000000006659
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of DWI in patients with ovarian cancer

Abstract: Background:Diffusion weighted imaging (DWI) is recently developed for identifying different malignant tumors. In this article the diagnostic accuracy of DWI for ovarian cancer was evaluated by synthesis of published data.Methods:A comprehensive literature search was conducted in PubMed/MEDLINE and Embase databases on the diagnostic performance of DWI for ovarian cancer published in English. Methodological quality was evaluated following Quality Assessment for Studies of Diagnostic Accuracy 2 (QUADAS 2) tool. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…The other subgroup analysis showed that better sensitivity was achieved when considering only the gastrointestinal tumors, suggesting that DWI could perform better for PMs from gastrointestinal tumors than from ovarian tumors. This is supported by a previous meta-analysis that revealed 86% sensitivity and 81% specificity for PMs from ovarian cancer, [ 29 ] which are lower than in the present meta-analysis. A meta-analysis of patients with cervical cancer showed that PET-CT was better than DWI for the detection of positive lymph nodes.…”
Section: Discussionsupporting
confidence: 89%
“…The other subgroup analysis showed that better sensitivity was achieved when considering only the gastrointestinal tumors, suggesting that DWI could perform better for PMs from gastrointestinal tumors than from ovarian tumors. This is supported by a previous meta-analysis that revealed 86% sensitivity and 81% specificity for PMs from ovarian cancer, [ 29 ] which are lower than in the present meta-analysis. A meta-analysis of patients with cervical cancer showed that PET-CT was better than DWI for the detection of positive lymph nodes.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with other studies of the efficacy and relative efficacy of DWI/MRI in colorectal cancer [10,11], ovarian cancer [12,13] and stomach cancer [14,15], similar results are obtained, illustrating the reproducibility of the experiment regardless of the treatment center used, study protocols, and subjective evaluation of PCI ranking results. The obtained results allow us to recommend DWI/MRI for pre-operative staging at all three investigated localizations of the tumour process.…”
Section: Discussion Of the Resultssupporting
confidence: 71%
“…Furthermore, teratomas and endometriomas can be accurately diagnosed on conventional MRI and do not represent diagnostic challenges. Other studies (33)(34)(35) also demonstrated that DWI can differentiate malignancies from benign ovarian tumors. The evaluation methods in these previous studies were based on DWI sequences, a qualitative method that is particularly susceptible to researcher bias.…”
Section: Discussionmentioning
confidence: 88%